Propuesta metodológica para la elaboración de planes de gestión de proyectos para el desarrollo de centros educativos públicos sustentables. - Sáenz-Campos, William; Shedden-Harris, Mario (Instituto Tecnológico de Costa Rica, 2011)
According to the United Nations Program for Environment (UNEP), the construction industry is consuming 40% of energy, and a third of the resources of humanity, including 12% of sweet water consumption; it is also the generator of one third of the emissions of greenhouse gases and 40% of solid waste on the planet. The sustainability therefore is vital, based on the need to preserve the environment and natural resources in order to maintain them available for future generations. Based on the foregoing, arises the proposal to conform the Methodological Guide for the Preparation of Management Plans Construction of Sustainable Public Schools in the Dirección de Infraestructura y Equipamiento Educativo (DIEE), which is the organ of the Public Education Ministry, responsible for the development of educational infrastructure projects needed by public schools in Costa Rica. Given the functional organizational structure of DIEE, it is proposed to incorporate the project management system through the creation of an internal executive unit on the Research and Development Department, in order to give continuity to the sustainable projects in all its phases and to have the power to create a base of updated information of the process assets generated during the conduct of such projects. This information would allow the use of inputs to incorporate green features to the prototypes that feed the functional flow DIEE work inputs, allowing the gradual inclusion of advances treated in sustainability to all the projects.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos,2011.
Keywords: Construcción; Sustentabilidad; Información; Usuarios; Flujo de datos; Prensa